Impact of oral early antiviral therapies for mild–moderate COVID-19 in the outpatient’s setting during Omicron era: a pharmacoeconomic analysis - Vincenzo Scaglione; Samuele Gardin; Lolita Sasset; Nicolò Presa; Alberto Rossetto; Deris Gianni Boemo; Sofia Silvola; Umberto Restelli; Annamaria Cattelan (European Journal of Medical Research)
Abstract Background Molnupiravir (MOL) and nirmatrelvir/ritonavir (NIR) decreased mortality and hospital admissions in high-risk patients with mild to moderate COVID-19. Nevertheless, there is a lack of data about the pharmacoeconomic impact of these antivirals in the Omicron era. We conducted a pharmacoeconomic analysis assessing the medical costs of the use of these antivirals compared to those occurred in people who refused the treatment. Methods The study included the first 50 patients vaccinated against SARS-CoV-2 of each month who experienced mild to moderate COVID-19 and were consecutively treated with oral antivirals at Padua University Hospital between February 1, 2022, and June 30, 2022. In addition, all consecutive patients who met the criteria for antiviral therapy during this period but opted not to receive treatment were included as control group. The two groups were compared in terms of costs associated with emergency department visits and hospitalizations, which were identified as the primary outcomes of the study. Results Nine-hundred-sixty-one patients were analysed, mean age was 67.72 ± 15.19 years and 49% were males. The most prevalent comorbidities were cardiovascular disease (57%), obesity (18) and diabetes mellitus (18%). Two-hundred-fifty-one (26%) patients were treated with MOL (group A), 252/961 (26%) were treated with NIR (group B) and 458/961 (48%) refused antiviral therapy (group C). While a generally more favourable outcomes was observed in the early treated group, no statistically significance differences between hospitalization or emergency department visits were found between group A and C and between group B and C. Total direct medical costs were statistically significantly higher both comparing group A (671.42 ± 460€) vs. group C and comparing group B (1008.42 ± 1562€) vs. group C (446.58 ± 4977€). The main cost driver associated with the increased cost was the antiviral therapy. The average hospitalization cost was 19,334.3 ± 27,030€ for group C, 8956.2 ± 7412€ for group B and 10,267.2€ for group A. Conclusions In the context of the Omicron variant during the COVID-19 pandemic, the use of early oral antiviral agents in vaccinated individuals was found to be more expensive compared to avoid treatment, primarily due to the high costs associated with it. To enhance the efficiency in resource allocation, it is essential to pursue policies aimed at reducing drug costs, along with conducting further pharmaco-economic studies.